2012
DOI: 10.1155/2012/638391
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Laterally Spreading Colorectal Tumors by Using Image-Enhanced Endoscopy

Abstract: Laterally spreading tumors may sometimes evade detection by colonoscopy. This study aimed to evaluate the use of image-enhanced endoscopy for visualizing laterally spreading tumors of the nongranular type. We reviewed consecutive patients with 47 non-granular-type laterally spreading tumors that had been examined using white-light imaging, autofluorescence imaging, narrow-band imaging, and chromoendoscopy with indigo carmine. The quality of visualization was evaluated using a 5-point scale by less- and more-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Our results revealed that AFI provided visibility comparable to that of CE. Tamai et al . reported that AFI provided high‐quality visualization of laterally spreading tumors non‐granular type.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that AFI provided visibility comparable to that of CE. Tamai et al . reported that AFI provided high‐quality visualization of laterally spreading tumors non‐granular type.…”
Section: Discussionmentioning
confidence: 99%
“…Tamai et al . reported that significantly better visualization of non‐polypoid colorectal lesions was provided by AFI than by WL when used by less‐experienced endoscopists . On the assumption that better differentiation and visualization may enable improved detection, we carried out the present pilot study to evaluate whether the AFI system is useful for trainees with an initial brief training session.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the identification of smaller neoplasms when reviewed by trainees was similar between the two systems. The AFI system has been shown to provide significantly better visualization and differentiation of non‐polypoid colorectal neoplasms than that provided by WL colonoscopy, which is an advantage of the AFI system . Any type of IEE, including AFI and NBI, has its own special characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several reports, the effectiveness of AFI systems for detecting colorectal neoplasia has been evaluated using first-generation AFI systems (EVIS LUCERA CLV-260SL, EVIS LUCERA CV-260S; Olympus Medical Systems, Tokyo, Japan); however, these results are controversial. [1][2][3][4] Recently, second-generation AFI systems have been developed (EVIS LUCERA ELITE CLV-290SL, EVIS LUCERA ELITE CV-290; Olympus Medical Systems) that have a brighter lamp and an improved image-processing algorithm that results in a higher frame rate and higher resolution images compared to those of the first-generation systems. According to a recent report, the second-generation AFI systems allow higher color contrast between colorectal neoplasia and the surrounding mucosa than white light imaging (WLI) and narrow band imaging.…”
mentioning
confidence: 99%